Nyckelharpa z Wolina. Przyczynek do historii instrumentów strunowych w średniowiecznej Europie - Janowski, Andrzej; Popławska, Dorota; Mazurek, Stanisław; Szychowska-Krąpiec, Elżbieta (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2015)
The text presents the results of a functional analysis and interpretation of a wooden object discovered during archaeological works in Wolin. According to the authors of the article, it is the top plate of the soundboard of a stringed instrument called the nyckelharpa. The results of a radiocarbon test indicate that the Wolin instrument is now the oldest known instrument of this type.